Efficacy and safety of moxibustion treatment for upper extremity pain disorder and motor impairment in patients with stage I post-stroke shoulder-hand syndrome: a systematic review and meta-analysis of randomized controlled trials - Xiaonan Meng; Xiaonan Meng; Jie Sun; Xintong Su; David Jung Seto; David Jung Seto; Liping Wang; Ying Li; Haikuo Yu; Baixiao Zhao; Jiping Zhao (Frontiers in Neurology)
BackgroundUpper extremity pain disorder and motor impairment (UE-PDMI) in patients with stage I post-stroke shoulder-hand syndrome (SHS) is a common neurological comorbidity. Current interventions are with effect limitations or side effects. Moxibustion is utilized as an integrative treatment for UE-PDMI. A novel meta-analysis should be performed due to the increasing number of relevant randomized controlled trials published recently. This study aims to evaluate the efficacy and safety of moxibustion treatment for UE-PDMI.MethodsEight databases, including the Cochrane Library, Embase, PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), SinoMed database, China Science and Technology Journal Database (VIP) and WanFang database, were systematically searched, from their inception through May 15 2024, to identify potentially relevant randomized controlled trials (RCTs) on moxibustion for UE-PDMI in SHS patients. The data from the eligible RCTs was extracted by two independent investigators. The RevMan software (version 5.4.1) was employed for conducting the meta-analysis. The online GRADEpro tool was applied for rating the quality of evidence.ResultsA total of 32 RCTs, involving 2,814 patients with UE-PDMI, were included. The favorable results were considered to be reflected by reduced scores on a visual analog scale (VAS) (mean difference [MD] = −1.68, 95% CI − 2.08, −1.28, p < 0.05), improved scores on the Fugl-Meyer Assessment of the Upper Extremity (FMA-UE, MD = 8.76, 95% CI: 7.00, 10.53, p < 0.05), higher scores on the modified Barthel index (MBI, MD = 10.27, 95% CI: 6.16, 14.34, p < 0.05) or Barthel index (BI, MD = 8.06, 95% CI: 6.20, 9.91, p < 0.05), and lower scores for functional impairment on National Institute of Health Stroke Scale (NIHSS, MD = −2.34, 95% CI: −2.96, −1.72, p < 0.05) when moxibustion was combined with rehabilitation training (RT), in contrast to control groups that implemented RT alone. The better total effective rates (TERs) were achieved when moxibustion was combined with RT (risk ratio [RR] = 1.27, 95% confidence interval [CI]:1.21, 1.33, p < 0.05) or with western medicine (RR = 1.18, 95% CI: 1.02, 1.35, p = 0.02) in comparisons to corresponding control groups. There was no significant difference in the occurrence of adverse events (AEs) between corresponding experimental and control groups (RR = 1.62, 95% CI: 0.63, 4.16, p > 0.05).ConclusionThis study demonstrates that moxibustion as an adjuvant therapy may play a positive role in relieving pain and improving upper extremity motor function for patients with stage I SHS, given its convenience in generating prolonged effects in communities. However, a larger number of rigorously designed, pre-registered RCTs are highly needed to verify its clinical efficacy with a higher level of certainty.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier [CRD42024601605].